Praktik Pemberian Makan Sebagai Faktor Penyebab Stunting pada Balita: Sebuah Narrative Review - Sri Hendrawati; Rahmawati Nur Baeti (Jurnal Keperawatan Galuh, 2025)
Stunting is Indonesia's most significant nutritional problem, with an incidence rate that tends to increase, reaching 29.6%. One of the causes of stunting is inappropriate feeding. It is influenced by social, cultural, and economic factors. This literature study purposed to identify toddlers feeding practice to the incidence factors of stunting. This literature study method is a narrative review. The framework of the narrative review process, according to Ferrari (2015), consists of five stages, namely identifying scientific literature in the database, identifying keywords, selecting articles database, identifying keywords, selecting articles, writing the results and discussion. Articles were collected from Cinahl, Pubmed, and Google Scholar. The keywords used were "mother" or "parent" and "feeding practice" and "parenting" and “stunting” by boolean "OR" and "AND" and in Indonesian namely feeding practices by mothers on stunting toddlers. The inclusion criteria were articles in Indonesian or English, published in 2011-2021, has an abstract, free full text, and located in Indonesia. The literature study found 58,849 articles, and only 10 articles met the criteria and were reviewed. Feeding practice that related to incidence factors included permissive parenting in feeding, early/ late complementary feeding, inadequate nutrition of complementary feeding, and mother’s lack of knowledge about toddler nutrition. Future research needs to assess further factors associated with feeding practices, such as economic, social and cultural factors.